Towards designing improved cancer immunotherapy targets with a peptide-MHC-I presentation model, HLApollo - William John Thrift; Nicolas W. Lounsbury; Quade Broadwell; Amy Heidersbach; Emily Freund; Yassan Abdolazimi; Qui T. Phung; Jieming Chen; Aude-Hélène Capietto; Ann-Jay Tong; Christopher M. Rose; Craig Blanchette; et al. (Nature Communications)
Abstract Based on the success of cancer immunotherapy, personalized cancer vaccines have emerged as a leading oncology treatment. Antigen presentation on MHC class I (MHC-I) is crucial for the adaptive immune response to cancer cells, necessitating highly predictive computational methods to model this phenomenon. Here, we introduce HLApollo, a transformer-based model for peptide-MHC-I (pMHC-I) presentation prediction, leveraging the language of peptides, MHC, and source proteins. HLApollo provides end-to-end treatment of MHC-I sequences and deconvolution of multi-allelic data, using a negative-set switching strategy to mitigate misassigned negatives in unlabelled ligandome data. HLApollo shows a 12.65% increase in average precision (AP) on ligandome data and a 4.1% AP increase on immunogenicity test data compared to next-best models. Incorporating protein features from protein language models yields further gains and reduces the need for gene expression measurements. Guided by clinical use, we demonstrate pan-allelic generalization which effectively captures rare alleles in underrepresented ancestries.